Adaptation of Technophobia and Technophilia Questionnaires into Russian - Yegor A. Dorokhov; Alexey N. Gusev (Lomonosov Moscow State University, 2023)
Background. Distrust of technology is an important barrier to its implementation into human life. In the research of attitude to computers and automated systems, special attention in psychological science has been paid to attitudes towards technology: technophobia and technophilia. Objective: The aim is to adapt two questionnaires to Russian sample in order to measure the technophobia and technophilia attitudes, as well as to evaluate their psychometric properties. Methods. The adaptation of the questionnaires was carried out in accordance with the requirements of psychometric standards. As part of the work, the methods of exploratory and confirmatory factor analysis were used to assess the internal structure of the techniques. Correlation analysis was used to obtain evidence supporting questionnaires validity. Sample. At the first stage of the study, 275 people filled out questionnaires on technophobia and technophilia, of which 194 were women (71 %) and 81 were men (29 %), the average age was 33.5 years (SD = 13.93). The second part of the study involved 545 employees of a large financial sector organization. Results. The methods showed sufficient reliability indicators on the scales (the Cronbach's α coefficient is higher than 0.8) and the expected correlation coefficients of the results on the questionnaires with each other and with questionnaires aimed at assessing personal anxiety, self-efficacy and personality traits (HEXACO). The internal structure of the adaptation of the questionnaires was analyzed with confirmatory and exploratory factor analysis. However, the hypothesis of the stability of the internal structure for each scale was not confirmed. Conclusion. Adapted questionnaires can be used for research purposes. It is necessary to continue collecting empirical data on both questionnaires. Practical application of the results. The proposed versions of the questionnaires can be used to assess technophobic and technophilic attitudes without dividing these scales into subscales. The authors have proposed an alternative version of dividing items into subscales for the technophobia questionnaire, while this version is considered as potentially more suitable, although it requires additional analysis on new data sets.